Game Addiction, the Impostor Phenomenon, and Social Adjustment Among Young Adults in India - Fenn, Jessy; Jegi, Jain P; Nandan, H Deva (UI Scholars Hub, 2024)
During the COVID-19 pandemic, online gaming grew rapidly, becoming a social lifeline for many youths confined to their homes while turning others into gaming addicts. Online gaming not only led to connections with other youths but also opened the gates to fantasy worlds filled with adventures and missions that could be accomplished with quick thinking and quick fingers. Success there could lead to further addiction and inversely affect gamers’ real-world social life. Could the gap between their online success and their social adjustment in the real world manifest itself as feelings of being an impostor? The aim of this research is to study 1) the relationships between game addiction and the impostor phenomenon, 2) game addiction and social adjustment, and 3) the mediating effect of social adjustment. The study includes 376 gamers between the ages of 18 and 25. The results show a strong positive relationship between gaming addiction and the impostor phenomenon, with males presenting higher levels of gaming addiction and the imposter phenomenon than females. Gaming is negatively related to males’ social adjustment. Females have higher levels of social adjustment, and the relationship between gaming and the impostor feeling is weaker for them. Social adjustment partially mediates the relationship between gaming and the impostor phenomenon.